Lateral Path Tracking in Limit Handling Condition using SDRE Control - Wachter, Erik (My University, 2016)
Tires operated at or close to their friction limits show a highly nonlinear force response. This state is called limit handling condition. The objective of this research is to minimize lateral path tracking error whilst the tires operate in limit handling. The State Dependent Riccati Equation (SDRE) technique is employed to develop a feedback-feedforward steering controller. It gives a systematic approach to take into account model nonlinearities such as combined slip tire characteristics. Furthermore the controller was implemented on real-time hardware and tested on a test track. The controller shows reliable path tracking performance up to the friction limits and also for conditions with large body sideslip angle, also referred to as ”Drifting”. Additionally a linear throttle controller was implemented to achieve autonomous body slip control on top of the path control. Experimental evaluation of this controller also showed promising results in terms of combined position and vehicle state control.
Keywords: Transport; Reglerteknik; Farkostteknik; Transport; Control Engineering; Vehicle Engineering